Structure, Management, and Intervention. Final Report. A Study of Selected Developing Colleges and Universities - St. John, Edward P.; Harvard Univ., Cambridge, MA. Graduate School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
This pilot study proposed and tested an institutional development model for use under the provisions of Title III of the Higher Education Act of 1965. The model could be used to improve the funding process and as a basis for future studies of the effects of the program. The study used a broad concept of management that incorporates all aspects of institutional development funded by Title III. The model proposes five phases of structural development with correspondingly different management systems. Testing was done in five colleges and Universities funded by the Advanced Institutional Development Program. Based on the study's findings it is possible to suggest plateaus of development for the planning, management, evaluation, and inquiring systems for institutions in each of four developmental phases, and that change strategies vary in effectiveness according to developmental phases. (MSE)
Availability: Office of Planning, Budgeting, and Evaluation, Office of Education, Room 4087, 400 Maryland Avenue SW, Washington, DC 20202.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Office of Planning, Budgeting, and Evaluation.
Contract Number: 41-676-7040-2.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administration; College Administration; Developing Institutions; Developmental Stages; Educational Change; Higher Education; Institutional Administration; Models; Organizational Development; Planning; Theories; Higher Education Act Title III -- Institutional Development; Reports, Research